Analysis of the Accounting Information System for the Sihuik – Huik Village APBD - Anggreni Siagian, Sofia; Fadhila Rahma, Tri Inda; Syafina, Laylan (Journal of Management, Economic, and Accounting, 2023)
This study aims to understand and analyze the implementation of the ABBDes accounting information system implemented by the Sihuik-Huik Village Government. To understand and analyze the constraints and suggestions on the implementation of the ABBDes accounting information system implemented by the Sihuik-Huik Village Government. Judging from the variety of data and this research applies qualitative descriptive research, qualitative research is research that produces explanatory data in the form of recorded or spoken words from individuals and the behaviors studied. The results of the study prove that accountability regarding the security of information data on the Sihuik - Huik Village APBDes implementation report is in accordance with a good accounting information system because the data is stored in an office computer and can only be opened by limited parties. Accountability for the timeliness of conveying information on the implementation of the Sihuik-Huik Village APBDes is not yet in accordance with a good accounting information system because there are still delays in compiling and conveying information to residents according to the stipulated time period. The effectiveness of the thorough preparation of data on the Sihuik-Huik Village APBDes implementation report is in accordance with a good accounting information system. The transparency of the variations in the APBDes implementation report used by the Sihuik-Huik Village Government is in accordance with a good accounting information system. The relevant transparency of the data provided and reported by the Sihuik-Huik Village Government regarding the implementation of the APBDes is in accordance with a good accounting information system because the data reported is relevant to the specified budget data. In accordance with the results of the research, suggestions were given to the Sihuik-Huik Village Government to carry out special training for village officials who work in compiling reports on the implementation of the APBDes and promoting unity among village apparatus when preparing reports on the implementation of the APBDes.